1997
DOI: 10.1200/jco.1997.15.4.1333
|View full text |Cite
|
Sign up to set email alerts
|

Delayed administration of dexrazoxane provides cardioprotection for patients with advanced breast cancer treated with doxorubicin-containing therapy.

Abstract: DZR is a highly effective cardioprotective agent when used in patients with advanced breast cancer who continue to receive doxorubicin-based chemotherapy after a cumulative doxorubicin dose of 300 mg/m2 has been reached.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
118
0
3

Year Published

1998
1998
2009
2009

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 237 publications
(123 citation statements)
references
References 6 publications
2
118
0
3
Order By: Relevance
“…every 3 weeks and were randomized to receive either DZR (500 mg/m 2 or 1000 mg/m 2 ) or placebo. 2,3 There was no maximum dose for doxorubicin, and no patients had received anthracyclines previously. The protocols for Studies 088001 and 088006 were identical.…”
Section: Patient Characteristicsmentioning
confidence: 99%
See 3 more Smart Citations
“…every 3 weeks and were randomized to receive either DZR (500 mg/m 2 or 1000 mg/m 2 ) or placebo. 2,3 There was no maximum dose for doxorubicin, and no patients had received anthracyclines previously. The protocols for Studies 088001 and 088006 were identical.…”
Section: Patient Characteristicsmentioning
confidence: 99%
“…2,3 The results of those studies indicated that DZR provided significant cardioprotection, 2 even if treatment started after a cumulative doxorubicin dose of 300 mg/m 2 had been administered. 3 The 2.2% incidence of doxorubicin-related CHF reported by Von Hoff et al 1 may not have been an accurate reflection of the true incidence of this adverse event.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…The addition of cardioprotective drugs such as dexrazoxane increases myelotoxicity [22] and thus probably results in limited treatment efficacy [23]. Also, the CNOP protocol with mitoxantrone substituting doxorubicin was significantly inferior to cyclophosphamide, hydroxydaunorubicin, oncovin, and prednisone (CHOP) regarding response rate and slightly inferior overall survival [24].…”
Section: Introductionmentioning
confidence: 99%